2021
DOI: 10.3390/ijms22157861
|View full text |Cite
|
Sign up to set email alerts
|

Reversing the Psychiatric Effects of Neurodevelopmental Cannabinoid Exposure: Exploring Pharmacotherapeutic Interventions for Symptom Improvement

Abstract: Neurodevelopmental exposure to psychoactive compounds in cannabis, specifically THC, is associated with a variety of long-term psychopathological outcomes. This increased risk includes a higher prevalence of schizophrenia, mood and anxiety disorders, and cognitive impairments. Clinical and pre-clinical research continues to identify a wide array of underlying neuropathophysiological sequelae and mechanisms that may underlie THC-related psychiatric risk vulnerability, particularly following adolescent cannabis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 121 publications
1
5
0
Order By: Relevance
“…For instance, previous studies have shown that rats with a history of cocaine, amphetamine, or morphine exposure exhibit an increased willingness to exert effort for palatable food reward (Forouzan et al 2021; Mendez et al 2009; Nordquist et al 2007b; Rouibi and Contarino 2012), as was observed in the current study after repeated THC exposure. This heightened motivation is thought to be mediated by increased mesolimbic dopamine signaling (Berridge and Robinson 2016; Robinson and Berridge 1993), which is consistent with previous reports that repeated THC exposure causes long-lasting hyperactivity in mesolimbic dopamine neurons (De Felice and Laviolette 2021; Renard et al 2017a), and sensitizes dopamine release in the nucleus accumbens core (Cadoni et al 2008).…”
Section: Discussionsupporting
confidence: 90%
“…For instance, previous studies have shown that rats with a history of cocaine, amphetamine, or morphine exposure exhibit an increased willingness to exert effort for palatable food reward (Forouzan et al 2021; Mendez et al 2009; Nordquist et al 2007b; Rouibi and Contarino 2012), as was observed in the current study after repeated THC exposure. This heightened motivation is thought to be mediated by increased mesolimbic dopamine signaling (Berridge and Robinson 2016; Robinson and Berridge 1993), which is consistent with previous reports that repeated THC exposure causes long-lasting hyperactivity in mesolimbic dopamine neurons (De Felice and Laviolette 2021; Renard et al 2017a), and sensitizes dopamine release in the nucleus accumbens core (Cadoni et al 2008).…”
Section: Discussionsupporting
confidence: 90%
“…However, in our experiments, different sets of animals underwent PIT, Pavlovian conditioned approach, and cocaine SA, so future experiments should be performed to directly check this correlation in the same subjects. Given that dopamine transmission in the NAcc is crucial for the PIT phenomenon, with a particular role of D1 receptors ( Lex and Hauber, 2008 ), the specific enhancement of PIT in the THC-exposed males observed here may be related to the hyperdopaminergic state induced by ACE in specific circuits ( De Felice and Laviolette, 2021 ), especially the increment in D1 receptors in the NAcc shell in males but not females after ACE observed by us in a previous report ( Higuera-Matas et al, 2010 ).…”
Section: Discussionmentioning
confidence: 47%
“…We next examined expression levels of several molecular signaling pathways known to be disrupted following neurodevelopmental adolescent THC exposure and dysregulated in neuropsychiatric disorders ( Ohtsuki et al, 2001 ; Madras, 2013 ; Urs et al, 2017 ; Renard et al, 2018 ; Szkudlarek et al, 2019 ; De Felice and Laviolette, 2021 ). Given that our VTA data revealed significant disruptions in DAergic activity states, we first characterized intra-NAc DA D1/D2R expression patterns.…”
Section: Resultsmentioning
confidence: 99%